Three new species of Anchocerus Fauvel (Coleoptera: Staphylinidae: Staphylininae), with an updated key to Chinese species - Hu, Jiayao; Li, Lizhen; Zhao, Meijun (Zootaxa, 2012)
Three new species of the genus Anchocerus Fauvel, A. pengzhongi & Li, sp. n.(Guangxi), A. yunnanensis Hu & Li, sp. n. (Yunnan) and A. yini Hu & Li, sp. n. (Yunnan) are described and illustrated from Southwest China. A key to all seven known species of the genus from China is provided.